Physical chemicals and rheologicals characterization of corn starch (zea mays l.) landraces popcorn (Research, Society and Development, 2021)
Starch is a substance considered biodegradable and widely used in the food industry as it is low cost and abundant in nature. Properties such as gelatinization, retrogradation, swelling power, solubility and water holding capacity can interfere with food preparation. Thus, the present work aimed to extract cornstarch (Zea Mays L.) creole popcorn by wet grinding as well as to determine its proximal composition, in addition to evaluating its rheological behavior and thermal properties under different processing conditions. The extraction yield of starch from colored popcorn (Zea Mays L.) corn was 6.3%. Its characteristics are common to many starches, but also different, such as the low acidity that favors its use to increase viscosity in other industrialized products. The sizes and shapes of the granules verified by SEM (Scanning Electron Microscopy) justify their viscoelastic behavior and rheological characteristics. Likewise, they may have contributed to their loss of mass along with their protein and lipid levels. The lipid concentration was also decisive in the gelatinization of the starch in the present study. Infrared spectroscopy confirmed that colored popcorn starch (Zea Mays L.) typically behaved like other starches, as well as its crystallinity. Thus, the Creole corn for the extraction of this starch is of a Creole species and potentially cultivable by family farming and in an agroecological system, incorporating sustainable characteristics.